Цифрові трансформації освіти: роль штучного інтелекту в модернізації освітньо-інформаційних послуг університетської бібліотеки (презентація) - Кічук, Надія Василівна; Демченко, Ольга Миколаївна; Щетиніна, Світлана Володимирівна (Ukrainian State University of Science and Technologies, Dnipro, 2024)
UKR: Окреслено деякі обриси нової бібліотечної моделі – “Бібліотека 4.0” (утворення “читач, бібліотекар, технології ШІ”). Здійснено певні узагальнення стосовно особливостей університетських бібліотек: важливість опори на принципи комфортності, доступності та інформативності у діяльності; загострення проблеми оптимізації самостійної навчальної роботи здобувачів як чинника якості освітнього процесу; актуалізація аспекту сформованості у користувачів базових “м’яких навичок”.

ENG: Some outlines of the new library model – "Library 4.0" (formation "reader, librarian, AI technologies") are described. Certain generalizations were made regarding the peculiarities of university libraries: the importance of relying on the principles of comfort, accessibility and informativeness in activities; aggravation of the problem of optimizing applicants’ independent educational work as a factor of the educational process’s quality; actualization of the aspect of basic "soft skills" formation among users.
Digital Transformations of Education: the Role of Artificial Intelligence in the Modernization of Educational and Information Services of the University Library (presentation)
Н. Кічук: ORCID: 0000-0002-5963-7802; О. Демченко ORCID 0000-0002-4083-2798; С. Щетиніна: ORCID 0009-0000-4709-863X
Keywords: цифрові трансформації; бібліотечна модель; іміджевість університетських бібліотек; здобувач вищої освіти; digital transformations; library model; image of university libraries; higher education applicant; presentstion; SOCIAL SCIENCES; SOCIAL SCIENCES::Other social sciences::Library and information science